A Study on Autopsy Findings of Different Types of Poisoning Cases at NRSMCH Morgue WHO Admitted and Expired at NRS Medical College Hospital, Kolkata - Sandip Mukhopadhyay; Sayak Sovan Dutta; Apurba Biswas (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Poisoning constitutes a major number of hospital admissions among different types ofhospital admission cases in India. Several factors like development of science along with invention of stronginsecticides and change in life style of human beings added with mental & social stress and easy availabilityof poisons are few factors responsible for increasing number of poisoning cases. The cause and the nature ofpoisoning cases which are admitting in different hospitals many times remain unknown to us. This problemcan be solved by examining different autopsy findings of different poisoning cases & chemical analysis ofdifferent organs as early as possible. The main objective of the study is to study both the external and internalautopsy findings in case of death due to poisoning. Methods: 74 poisoning cases were studied over a periodof one year who were first admitted in NRSMCH and subsequently died at the said Hospital. Brought deathand nursing home/other Hospital admission cases/ cases referred from other Hospital are excluded from thisstudy. The study is a prospective, cross sectional and descriptive study. Conclusion: Corrosive poisoningis the commonest type of poison followed by ophitoxaemia. Face was congested in most cases of death. Nosignificant findings found in most of the victim’s oesophagus. Majority of internal organs were congested.